OPTIMIZATION OF DYNAMIC SHADING SYSTEM ON OPEN-PLAN OFFICE AT BANDUNG DEPARTMENT OF LIBRARY AND ARCHIVES - Kusuma Dewi (13314063), Annisa Azalia Herwandani (13314071) , Deasty
of daylight in open-plan office will give positive impact as it will creates healthy work environment and increases user productivity. Located at the third floor of Bandung Municipal Service of Library and Archives building, the Department of Women’s Empowerment and Child Protection office has west facade that can potentially cause glare at the nearest area and inequality of illuminance on workplane of the room, so that internal shading devise are required. This research is focused on internal shading device optimization in order to maintain spatial daylight autonomy (sDA300/50%) value over 55%, annual sunlight exposure (ASE1000,250) value under 10%, and %DGP>0,21 under 50% by utilizing Grasshopper software to create simulation. Four types of dynamic shading device are added to optimization based on solar radiation category, (1) 1~80 W/m2, (2) 81~159 W/m2, (3) 160~289 W/m2, and (4) 290~541 W/m2 with input parameters form, slat angle, and material specularity. The result shows that sDA300/50% can be maintained above 55%, ASE1000,250 value reduced, and %DGP>0,21 value increased 50% from initial condition. The optimal solution for each solar radiation category obtained from Pareto front, are 90° slat angle for horizontal shading device with 0,9 specularity and 90° slat angle fro vertical shading device with 0,4 specularity for category 1, 75° slat angle for horizontal shading device with 0,8 specularity and 75° slat angle for vertical shading device with 0,2 specularity for category 2, 60° slat angle for horizontal shading device with 0,8 specularity and 60° slat angle for vertical shading device with 0,2 specularity for category 3, and 45° slat angle for horizontal shading device with 0,9 specularity and 30° slat angle for vertical shading device with 0,4 specularity for category 4.